Validation of a non-verbal communication protocol for nursing consultations with blind people - Cristiana Brasil de Almeida Rebouças; Lorita Marlena Freitag Pagliuca; Namie Okino Sawada; Paulo César de Almeida (Universidade Federal do Ceará, 2012)
This research is aimed at validating a non-verbal communication model for the delivery of nursing care to blind patients, in line with the theoretical framework developed by Hall. It was developed at the Health Communication Laboratory of the Nursing Department at the Federal University of Ceará, Brazil between October 2007 and June 2008. It is a methodological research due to the validation of a protocol of nonverbal communication. The Non-Verbal Communication Protocol was constructed and submitted to three communications specialists for analysis and validation of the content. To test the validity of nonverbal communication protocol the subjects were divided into two groups which contained 15 nurses and 15 blind people. The protocol was entirely developed by the authors based on literature review. The nursing consultations were subdivided into four steps, called care steps. This research concluded that the protocol is valid for application in nursing practice.